2017
DOI: 10.1177/0091450917723770
|View full text |Cite
|
Sign up to set email alerts
|

Addiction Frameworks and Support for Expanding Treatment for Drug Offenders

Abstract: This study examined how a respondent's addiction framework (i.e., whether they conceptualized addiction as a medical-social or a moral problem) was associated with their attitudes toward expanding treatment for drug offenders via funding for California's Proposition 36. Using a 2012 California Field Poll, the author created scales to assess an individual's addiction framework. Logistic regression was used to assess how well the addiction frameworks correlated with support for expanding Proposition 36. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…Previous research conducted by Murphy (2017) and others (Murphy & Russell, 2020; has demonstrated stigma-influenced attitudes in law enforcement, the public, and students enrolled in criminal justice and nursing. Thirteen items were chosen from previous research to assess drug use stigma in the current study.…”
Section: Stigmamentioning
confidence: 96%
See 2 more Smart Citations
“…Previous research conducted by Murphy (2017) and others (Murphy & Russell, 2020; has demonstrated stigma-influenced attitudes in law enforcement, the public, and students enrolled in criminal justice and nursing. Thirteen items were chosen from previous research to assess drug use stigma in the current study.…”
Section: Stigmamentioning
confidence: 96%
“…This scale is comprised of 4 items designed to measure endorsement of the medical/ disease model of addiction. Items were based on previous research (see Murphy, 2017). All items were measured on a 5-point scale where 1 ¼ strongly disagree to 5 ¼ strongly agree.…”
Section: Endorsement Of the Disease Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on this literature base, the primary objective of the current study was to empirically examine the relationship between addiction frameworks, opioid-related stigma, and policy-related attitudes (i.e., NIMBY syndrome, support for punitive treatment of OUD, support for employment discrimination against individuals prescribed MOUD). Given findings from previous studies (see Kruis et al, 2022;Murphy, 2017;Murphy & Russell, 2021), we hypothesized that there would be a significant direct positive relationship between opioid-related stigma and expressions of NIMBY syndrome for OUD treatment. We also hypothesized that there would be a significant direct negative relationship between support for the disease model of addiction and NIMBY syndrome found in baseline models that did not control for opioid-related stigma.…”
Section: Current Studymentioning
confidence: 98%
“…The main independent measure of inquiry in this study was support for the disease model of addiction. This variable, a measure of one's addiction framework, was conceptualized as a respondent's endorsement of opioid addiction being a medical problem (Murphy, 2017). To capture this variable, participants were asked to indicate their level of agreement with the following statement: "Opioid addiction is a medical illness like diabetes, arthritis, or heart disease."…”
Section: Stigmamentioning
confidence: 99%